Complete mitochondrial genome of the geniculate calcified red alga, Corallina officinalis (Corallinales, Rhodophyta). Issue 1 (1st January 2016) - Williamson, Christopher; Yesson, Christopher; Briscoe, Andrew G.; Brodie, Juliet
Abstract: We present the first mitochondrial genome of the calcified, geniculate coralline red alga Corallina officinalis (Corallinales). The circular genome consists of 26, 504 bp and has a gene content consisting of 23 protein-coding genes, 26 transfer RNA genes and two ribosomal RNA genes, with an overall GC content of 30.1%.